Workshop on Recognizing Text Structures and Making Notes of Graphic Organizer for Primary School Teachers in Sambas Regency - Djudin, Tomo; Hamdani, Hamdani; Firdaus, Muhammad; Syarif, Muhammad Musa; Habellia, Ray Cinthya (STKIP Singkawang, 2023)
Reading and taking notes are thinking processes. By combining the activity of reading the text and continuing with making notes, the cognitive structure and existing knowledge will be modified to accommodate the new knowledge. This study applied the quasi-experimental method with one-group posttest only design. The treatment of this study is implementation of workhop. Amount of 53 voluntary public primary school teachers atSambas regency-Westkalimantan-Indonesia in second semester of academic year 2021/2022 participated in this workshop. After the training, a six short-answers test, a six performance test, and a questionnaire were administered. The results revealed that all (100%) teachers have recognized the patterns of texts of squence, classification, and problem solution. However, amount of teachers (28.30%) did not recognize of the generalization pattern, 11.32% did not recognize the comparasion and contrast pattern, and some of them (20.75%) did not recognize of the enumeration pattern. Many teachers had succeed in making note of mnemonics. The participants argued that workshop aimed to improve quality of teaching-learning at school could be conducted in extensively at the future.